2022
DOI: 10.3390/molecules27123937
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Organic Extracts of the Genus Aristolochia: A Review from 2005 to 2021

Abstract: Different ethnomedicinal studies have investigated the relationship between various phytochemicals as well as organic extracts and their bioactive aspects. Studies on biological effects are attributed to secondary metabolites such as alkaloids, phenolic compounds, and terpenes. Since there have been no reviews in the literature on the traditional, phytochemical, and ethnomedicinal uses of the genus Aristolochia so far, this article systematically reviews 141 published studies that analyze the associations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…The informative data obtained from the analysis are summarized in Table S1 and Supplementary HPLC-UV and HRMS data. Magnoflorine (2), an aporphine derivative, and two aristolochic acids (AA)-I (7) and AA-II (6) were identified by complete concurrence with standard compounds. The mass spectrometric behavior of AAs was studied using standard compounds (AA-I and AA-II) and previously published information [56][57][58].…”
Section: The Effect Of Rolc and Rolb On Accumulation Of Phenanthroic ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The informative data obtained from the analysis are summarized in Table S1 and Supplementary HPLC-UV and HRMS data. Magnoflorine (2), an aporphine derivative, and two aristolochic acids (AA)-I (7) and AA-II (6) were identified by complete concurrence with standard compounds. The mass spectrometric behavior of AAs was studied using standard compounds (AA-I and AA-II) and previously published information [56][57][58].…”
Section: The Effect Of Rolc and Rolb On Accumulation Of Phenanthroic ...mentioning
confidence: 99%
“…Consequently, Aristolochia plants are considered "natural factories" for producing these phytochemicals [5]. For centuries, Aristolochia species have been utilized in traditional medicine across Asia to treat various ailments, such as arthritis, rheumatism, angina, and myocardial infarction, alone or in combination with other herbs [6]. Studies have also suggested their potential as analgesics, antimalarials, antibacterial agents, and antidotes for snake bites [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various species of Aristolochia have been reported to show antimicrobial activities [20]. Table 2 shows a varying degree of antimicrobial activity demonstrated by the four A. albida root extracts when investigated against the five microorganisms.…”
Section: Key: (+) = Slightly Present (++) = Moderately Present (+++) ...mentioning
confidence: 99%
“…Aristolochia is used especially in cases of gout, arthritis, rheumatism, and skin diseases, and can also be used to treat snakebites (Gifford et al, 2017;Perry & Metzger, 1980). A recent review on biological activities of the Aristolochia genus recognizes an even larger spectrum of effects of traditional preparations from different species, including anticancer, antibacterial and antiparasitic activities, among others (Lerma-Herrera et al, 2022). The phytochemistry of the genus has been widely investigated but lacks a systematic approach, usually including various organs from different plant species.…”
Section: Introduction 1the Genus Aristolochia: Between Poison and Med...mentioning
confidence: 99%